2015
DOI: 10.1016/j.nbd.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Degraded neural and behavioral processing of speech sounds in a rat model of Rett syndrome

Abstract: Individuals with Rett syndrome have greatly impaired speech and language abilities. Auditory brainstem responses to sounds are normal, but cortical responses are highly abnormal. In this study, we used the novel rat Mecp2 knockout model of Rett syndrome to document the neural and behavioral processing of speech sounds. We hypothesized that both speech discrimination ability and the neural response to speech sounds would be impaired in Mecp2 rats. We expected that extensive speech training would improve speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
62
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 54 publications
19
62
1
1
Order By: Relevance
“…Furthermore, because regression in RTT may also coincide with the loss of speech, it may be informative to determine whether the type and nature of ultrasonic vocalizations (USV) emitted by female Mecp2 ZFN/+  rats, or other aspects of communication, change over time. Although we did not find differences in the total number of USV emitted by juvenile female Mecp2 ZFN/+  rats during direct social interaction tests (data not shown), a recent study of symptomatic 5-11 month old female Mecp2 ZFN/+  rats found alterations in speech processing (80), suggesting that communication deficits, in a broader context, may be affected in this model.…”
Section: Discussioncontrasting
confidence: 75%
“…Furthermore, because regression in RTT may also coincide with the loss of speech, it may be informative to determine whether the type and nature of ultrasonic vocalizations (USV) emitted by female Mecp2 ZFN/+  rats, or other aspects of communication, change over time. Although we did not find differences in the total number of USV emitted by juvenile female Mecp2 ZFN/+  rats during direct social interaction tests (data not shown), a recent study of symptomatic 5-11 month old female Mecp2 ZFN/+  rats found alterations in speech processing (80), suggesting that communication deficits, in a broader context, may be affected in this model.…”
Section: Discussioncontrasting
confidence: 75%
“…Severe auditory cortex deficits have also been observed in the rodent Fmr1 knockout model of fragile X syndrome, the rodent valproic acid model of autism, and the rat Mecp2 knockout model of Rett syndrome (Gandal et al, 2010; Liao et al, 2012; Kim et al, 2013; Engineer et al, 2014a, 2014c, 2015a; Anomal et al, 2015). The auditory cortex responses observed in the Shank3 heterozygous rat model are weaker, which is consistent with other rat models of ASD.…”
Section: Discussionmentioning
confidence: 96%
“…Individuals with autism and genetic disorders, such as Rett syndrome, commonly exhibit receptive language deficits and cortical responses that are both weaker and slower [Bader, Witt-Engerstr€ om, & Hagberg, 1989;Stach, Stoner, Smith, & Jerger, 1994;Stauder, Smeets, van Mil, & Curfs, 2006;Gandal et al, 2010;Roberts et al, 2010]. Severe auditory cortex deficits have also been observed in the rodent Fmr1 knockout model of fragile X syndrome, the rodent valproic acid model of autism, and the rat Mecp2 knockout model of Rett syndrome [Gandal et al, 2010;Liao et al, 2012;Kim et al, 2013;Engineer et al, 2014aEngineer et al, , 2014cEngineer et al, , 2015aAnomal et al, 2015]. The auditory cortex responses observed in the Shank3 heterozygous rat model are weaker, which is consistent with other rat models of ASD.…”
Section: Relationship To Other Genetic Disorders and Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is paralleled in rodents; rats that were trained to use the repetition rate of noise pulses in order to find a target location exhibited enhanced A1 responses to rapid stimuli as well as stronger phase-locked responses [7]. Auditory training also greatly benefits rat models of disorders, such as autism or dyslexia [26,50]. Rats prenatally exposed to valproic acid are a well-studied autism model that exhibit significantly weaker and less synchronized responses to rapidly presented stimuli [51].…”
Section: Discussionmentioning
confidence: 99%